Retinopathy progression and the risk of end-stage kidney disease: results from a longitudinal Japanese cohort of 232 patients with type 2 diabetes and biopsy-proven diabetic kidney disease. Issue 1 (2nd November 2019) - Yamanouchi, Masayuki; Mori, Mikiro; Hoshino, Junichi; Kinowaki, Keiichi; Fujii, Takeshi; Ohashi, Kenichi; Furuichi, Kengo; Wada, Takashi; Ubara, Yoshifumi
Abstract : Objective: The predictive value of diabetic retinopathy on end-stage kidney disease (ESKD) has not been fully addressed in patients with type 2 diabetes and diabetic kidney disease. Research design and methods: We studied 232 patients with type 2 diabetes and biopsy-proven diabetic kidney disease who were screened for diabetic retinopathy during the 1 month of kidney biopsy. We examined the association between retinopathy progression and renal lesions. We used Cox regression analyses to explore the risk of ESKD adjusting for known risk demographic and clinical variables. We assessed the incremental prognostic value of ESKD by adding diabetic retinopathy to the clinical variables. Results: The diabetic retinopathy progression positively correlated with all scores of renal lesions, especially with the glomerular-based classification (r=0.41), scores of interstitial fibrosis (r=0.41) and diffuse lesion (r=0.48). During a median follow-up of 5.7 years, 114 patients developed ESKD. Adjusting for known risk factors of ESKD, the HR for ESKD (patients with no apparent retinopathy as a reference) were 1.96 (95% CI 0.62 to 6.17) for patients with mild non-proliferative diabetic retinopathy (NPDR), 3.10 (95% CI 1.45 to 6.65) for patients with moderate NPDR, 3.03 (95% CI 1.44 to 6.37) for patients with severe NPDR, and 3.43 (95% CI 1.68 to 7.03) for patients with proliferative diabetic retinopathy, respectively. Addition of the retinopathy grading to the clinical model alone improved the prognostic value (the global χ 2 statistic increased from 155.2 to 164.5; p<0.001), which is an improvement equivalent to the addition of the renal lesion grading to the clinical model. Conclusions: Retinopathy progression appeared to be associated with renal lesions and the development of ESKD. Our findings suggest that diabetic retinopathy and kidney disease share the same magnitude of disease progression, and therefore diabetic retinopathy may be useful for prognosticating the clinical course for diabetic kidney disease.